289. International Validation of a Methicillin-Resistant Staphylococcus aureus (MRSA) Risk Assessment Tool for Acute Bacterial Skin and Skin Structure Infections (ABSSSI). (26th November 2018) - Zasowski, Evan J; Trinh, Trang D; Claeys, Kimberly; Dryden, Matthew; Shlyapnikov, Sergey; Bassetti, Matteo; Carnelutti, Alessia; Khachatryan, Nana; Kurup, Asok; Cejudo, Abraham Pulido; Melo, Luiz Henrique; Cao, Bin; et al.
Abstract: Background: Anti-MRSA antibiotic under- and overprescribing for ABSSSI is common. To address this, we previously developed an MRSA risk assessment tool using prior literature and patient data from a single health system in Detroit, Michigan, USA. The objective of this study was to validate this risk assessment tool internationally. Methods: Multicenter, international, prospective cohort study. Inclusion: age ≥ 18 y; purulent ABSSSI from July 2016 to March 2018. Exclusion: no culture; osteoarticular infection; bite wounds; odontogenic infections. Patient MRSA risk scores were computed using the following criteria (point value): previous MRSA infection/colonization (2); previous hospitalization (1); previous antibiotics (1); chronic kidney disease (1); intravenous drug use (1); HIV/AIDS (1); diabetes with obesity (1). The likelihood ratio of each patient's score was used to convert local surveillance MRSA percentage (prior probability) into an individual patient estimated MRSA probability (posterior probability). The predictive performance of local surveillance MRSA percentage, MRSA risk score, and estimated MRSA probability were quantified using the area under the Receiver Operating Characteristic curve (aROC) and compared using the Hanley and McNeil method. Results: 203 patients from 7 international sites included. The most common infection types were wound (28.6%), abscess (25.1%), and cellulitis with an abscess (20.7%). MRSA was observed in 33% of patients and ranged from 10% in Beijing, CN to 58.8% in Mexico City, MX. MRSA was significantly more prevalent among patients with higher MRSA risk scores (Figure 1). The MRSA risk score aROC (95% CI) [0.748 (0.678–0.819)] was significantly greater than local surveillance MRSA percentage [0.646 (0.569–0.722)] ( P = 0.016). The estimated MRSA probability aROC [0.781 (0.716–0.845)] was significantly greater than local surveillance MRSA percentage ( P < 0.001) but not the MRSA risk score ( P = 0.192). Conclusion: The MRSA risk score and estimated MRSA probability were significantly more predictive of MRSA ABSSSI compared with local MRSA surveillance percentage. Further study, including potential impact of this MRSA risk assessment tool on prescribing patterns are required before widespread application. Disclosures: K. Claeys, Nabriva: Scientific Advisor, Consulting fee Melinta: Scientific Advisor, Consulting fee. M. Dryden, Motif BioSciences: Board Member, Consulting fee. M. J. Rybak, Allergan: Consultant, Grant Investigator and Speaker's Bureau, Research grant and Research support. Achaogen: Consultant, Grant Investigator and Speaker's Bureau, Consulting fee, Research grant and Research support. Bayer: Consultant, Grant Investigator and Speaker's Bureau, Consulting fee, Research grant and Research support. Melinta: Consultant, Grant Investigator and Speaker's Bureau, Consulting fee, Research grant and Research support. Merck: Consultant, Grant Investigator and Speaker's Bureau, Consulting fee, Research grant and Research support. Theravance: Consultant, Grant Investigator and Speaker's Bureau, Consulting fee, Research grant and Research support. Sunovian: Consultant, Grant Investigator and Speaker's Bureau, Consulting fee, Research grant and Research support. Zavante: Consultant, Grant Investigator and Speaker's Bureau, Consulting fee, Research grant and Research support. NIAID: Consultant, Grant Investigator and Speaker's Bureau, Consulting fee, Research grant and Research support.